Impact of the COVID-19 pandemic on risk of burn-out syndrome and recovery need among secondary school teachers in Flanders: A prospective study - Hannah De Laet; Yanni Verhavert; Kristine De Martelaer; Evert Zinzen; Tom Deliens; Elke Van Hoof (Frontiers in Public Health, 2022)
BackgroundDue to the COVID-19 pandemic, schools were closed, teachers had to teach from home and after a while, they had to return to the classroom while the pandemic was still on-going. Even before the pandemic, teachers were already more at risk for burn-out syndrome compared to the general population. Furthermore, not much research pertaining to this population has been carried out during the pandemic and so the impact of the pandemic on teachers' risk of burn-out syndrome and recovery need remains unclear. The aim of the current study was to fill this knowledge gap and map out the impact on risk of burn-out syndrome and recovery need at different time points during the pandemic.Methods and findingsAt baseline, 2,167 secondary school teachers in Flanders were included in this prospective study. Questionnaire data were obtained at ten different time points between September 2019 and August 2021. To assess risk of burn-out syndrome and its dimensions, the Utrecht Burn-out Scale for Teachers was administered. Need for recovery was assessed using questions adopted from the Short Inventory to Monitor Psychosocial Hazards. The results revealed an initial positive effect of the first lockdown (Mar/Apr 2020) with a decrease in risk of burn-out syndrome [Odds ratio (OR) Jan/Feb 2020–Mar/Apr 2020 = 0.33, p < 0.001], emotional exhaustion (EMM Jan/Feb 2020–Mar/Apr 2020 = −0.51, p < 0.001), depersonalization (EMM Jan/Feb 2020–Mar/Apr 2020 = −0.13, p < 0.001) and recovery need [Estimated marginal mean (EMM) Jan/Feb 2020–Mar/Apr 2020 = −0.79, p < 0.001]. No significant effect on personal accomplishment was found (p = 0.410). However, as the pandemic went on, higher risk of burn-out syndrome, emotional exhaustion, depersonalization and recovery need, and lower personal accomplishment were observed.ConclusionsDespite the initial positive impact on risk of burn-out syndrome, its dimensions and recovery need, a negative long-term impact of the COVID-19 pandemic became visible. This study highlights once again the importance for interventions to reduce teachers' risk of burn-out syndrome, especially in such difficult times as a pandemic.